Identification of Aquifers in Kuber Beach Tourism Area at Tual City - Andrias Latupapua (Faculty of Agriculture, Pattimura University, 2022)
The availability of clean water in the Kuber Beach tourist area is not known for certain. To determine the depth and characteristics of the aquifer, the rock resistivity measurement was carried out using the geoelectric method with Schlumberger configuration on two tracks with a span of 200 m each. The results showed that the semi-confined aquifer was at a depth below 8 m from the ground surface. Aquifers with sand lithology have low potential, while limestones have medium potential.